2020
DOI: 10.1371/journal.pone.0240124
|View full text |Cite
|
Sign up to set email alerts
|

Complete plastome assemblies from a panel of 13 diverse potato taxa

Abstract: The chloroplasts are a crucial part of photosynthesizing plant cells and are extensively utilized in phylogenetic studies mainly due to their maternal inheritance. Characterization and analysis of complete plastome sequences is necessary to understand their diversity and evolutionary relationships. Here, a panel of thirteen plastomes from various potato taxa are presented. Though they are highly similar with respect to gene order and content, there is also a great extent of SNPs and InDels between them, with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…Similarly, ADG2 and CHA mitogenomes are grouped together. The nuclear and plastome phylogeny of these 13 accessions was previously determined (Achakkagari et al 2020;Kyriakidou et al 2020), and a similar type of grouping was observed in these potato accessions. Also, a similar grouping of AJH, JUZ, and TBR accessions was observed in the plastome phylogeny.…”
Section: Phylogenetic Analysissupporting
confidence: 70%
See 3 more Smart Citations
“…Similarly, ADG2 and CHA mitogenomes are grouped together. The nuclear and plastome phylogeny of these 13 accessions was previously determined (Achakkagari et al 2020;Kyriakidou et al 2020), and a similar type of grouping was observed in these potato accessions. Also, a similar grouping of AJH, JUZ, and TBR accessions was observed in the plastome phylogeny.…”
Section: Phylogenetic Analysissupporting
confidence: 70%
“…chaucha (CHA) (CIP 2021l), and S. tuberosum subsp. tuberosum (TBR) (CIP 2021m)) grown at the International Potato Center (CIP) in Lima, Peru as described (Kyriakidou et al 2020), and sequenced using Illumina PE technology, except BUK2, which was sequenced with 10X Genomics' GemCode technology (https://www.10xgenomics.com/).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…The plastid DNA sequences (plastomes) of land plants are highly conserved compared to nuclear and mitochondrial DNA, and are extensively studied for their maternal phylogenetic relationships (Hosaka and Hanneman 1988). However, previous studies have shown considerable differences in plastomes and analysis of their complete sequences is important in understanding their diversity and evolutionary links (Hosaka 1986;Hosaka and Hanneman 1988;Chung et al 2006;Achakkagari et al 2020). In this study, a panel of nine diploid potato clones were selected for their unique characteristics such as tuber size, shape and disease resistance.…”
mentioning
confidence: 99%